Peritidal cyclic sedimentation from La Manga Formation (Oxfordian), Neuquén Basin, Mendoza, Argentina - Palma, Ricardo Manuel (2013)
The La Manga Formation consists of marine carbonates and represents most of the sedimentary record of the Callovian-Oxfordian in the Neuquén Basin. Three localities in the southern Mendoza province were studied and their cyclicity was determined by means of facies analysis and their vertical arrangement. Facies of inner ramp, that were deposited in extremely shallow-water environments with intermittent subaerial exposures have been broken down into shallow subtidal, and intertidal?supratidal environments. Shallow subtidal facies are arranged into decimetre scale upward-shallowing cycles composed of marls, laminated or massive mudstones or bioclastic wackestones and intraclastic wackestone-packstones. Intertidal-supratidal centimetre-scale cycles consist of an upward-shallowing succession of restricted facies, overlaid by horizontal o crinkle microbial laminites, flat pebble conglomerates or breccias beds. The defined cycles show a shallowing upward trend in which the evidence of relative sea-level lowering is accepted. The interpretation of Fischer plots allowed the recognition of changes in accommodation space.